1980
DOI: 10.1007/bf00268446
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the E. coli groNB (nusB) gene which affects bacteriophage λ N gene function

Abstract: Escherichia coli mutants, called groNB, which block the growth of bacteriophage lambda at the level of action of the gene N product, have been isolated as survivors at 42 degrees C of bacteria carrying a) the defective prophage lambda bio11 i lambda cI857 delta H1 or b) the pcR1 plasmid containing the EcoRI immunity fragment of phage lambda cI857. In addition, groNB bacterial mutants have been isolated at 37 degrees C, as large colony formers in the presence of lambda i lambda cI h434, lambda i lambda cI h lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Previous studies have indicated that the NusA and the NusB proteins are involved in various aspects of the regulation of E. coli transcription termination (29)(30)(31)(32)(33) and, since conditionally lethal mutations have been isolated in nusA (34) and nusB (35), it is clear that these proteins perform essential functions in the growth of E. coli cells. Our present results show that one such function may be antitermination of rRNA operon transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that the NusA and the NusB proteins are involved in various aspects of the regulation of E. coli transcription termination (29)(30)(31)(32)(33) and, since conditionally lethal mutations have been isolated in nusA (34) and nusB (35), it is clear that these proteins perform essential functions in the growth of E. coli cells. Our present results show that one such function may be antitermination of rRNA operon transcription.…”
Section: Discussionmentioning
confidence: 99%
“…Although NusB is not an integral ribosomal protein, it does influence translation, as shown by the observation that nusB mutants have slowed translation rates relative to wild type (Taura et aL, 1992), and is associated with ribosomes following high-salt wash (Das and Wolska, 1984). NusB null mutants have the interesting property of being cold sensitive for growth (Taura et aL, 1992;Georgopoulos et aL, 1980). At elevated temperatures, these nusB null mutants grow, but, as discussed above, exhibit reduced translation rates and a Nus-phenotype (Taura et al, 1992).…”
Section: Nusb and Nusementioning
confidence: 96%
“…Three E. coli strains with unrelated coldsensitive mutations were employed. CG431 carries the nusBl36(Cs) mutation (20). NusB, like NusA, has been implicated in transcription elongation (for a review, see reference 18).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, these physiological differences could result from differences between the requirements for growth at lower versus higher temperatures. Two examples of gene products that appear to be required only at low temperatures are those of the yeast SACi gene, an apparent component of the cytoskeleton (34), and the E. coli nusB gene, a transcription elongation factor (20). Moreover, in E. coli, cold-sensitive but not thermal-sensitive mutations affecting ribosome assembly could be isolated (22,48).…”
Section: Resultsmentioning
confidence: 99%